Ratio Decidendi District Court Decision in Case of Deed Not Read Based on Notary Position Law (Decision No 873/Pdt.G/2013/ Pn.Sby) - Gita Ayu Thaharah; Yenni Eta Widyanto; Fathul Laila (CV. AFDIFAL MAJU BERKAH, 2024)
This research is aimed at analyzing the Ratio Decidendi of District Court Decision No. 873/Pdt.G/2013/PN.Sby against notaries who do not read their deeds. The purpose of this research is to determine and analyze the Decidendi Ratio of District Court Decision No. 873/Pdt.G/2013/PN.Sby regarding deeds that were not read by a notary. Then to analyze the responsibilities of notary officials based on article 16 paragraph 1 letter (m) of the Law on Notary Positions. This type of research uses normative juridical research using a statutory approach and a conceptual approach using literature study legal material search techniques. The analysis technique used in this research is the interpretation technique used is systematic interpretation. Based on this, the problem formulation is (1) What is the judge's consideration (Ratio Decidendi) regarding Decision No. 873/Pdt.G/2013/PN.Sby regarding deeds that were not read by a notary? and problem formulation (2) What are the responsibilities of notary officials for deeds that are not read out based on article 16 paragraph 1 letter m based on the Law on Notary Positions? (1) Ratio Decidendi, namely the implementation of a decision with a ruling that the lawsuit cannot be accepted (Niet Ontvankelijk verklaard) in District Court Case No. 873/Pdt.G/2013/PN.Sby, even though in principle the lawsuit is not accepted, the notary still has responsibility for deed that he has made. Even though in principle the lawsuit is not accepted, the judge should consider not carrying out the obligation to read the deed by a notary(2) The Notary's responsibility for a deed that is not read, in this case the Notary can be sued because the authentic deed is downgraded to a private deed and then be sued civilly, namely regarding compensation based on 1365 of the Civil Code, as well as administrative sanctions based on the Code of Ethics. Notary. The advice that can be given is that during the examination of the case, if the lawsuit contains formal defects, it is better to stop it so that the decision is not rejected. Then the parties in the lawsuit must make a detailed lawsuit so that the lawsuit can be granted. Then there are administrative sanctions for the notary who does not carry out the obligation to read the deed. less severe and less of a deterrent effect, then the supervisory board should ensure that the deed made by the notary is truly authentic or not during its inspection and there should be a clear place for complaints for the public to the regional supervisory board.